Textbook of family practice - Rakel, Robert E. (W.B. Saunders Company, 2002)
Guides physicians through various aspects of their practice, offering advice to help encourage excellence, strengthen careers, and broaden patient bases. This book contains chapters on Clinical Guidelines; Evidence-Based Health Care; Practice-Based Research; Mind-Body Medicine; and other approaches and findings.